PERUBAHAN SISTEM NILAI BUDAYA MANDAILING DALAM NOVEL PUSARA KARYA MAULANA SYAMSURI ANALISIS SOSIOLOGI SASTRA - , Junita Irawati ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Research conducted by material objects novel Pusara by Maulana Syamsuri is against the background of Mandailing social phenomenon is revealed in the novel Pusara, which changes sistem Mandailing cultural values. Theoretically, the research aims to uncover the social conditions of society Mandailing contained in the novel Pusara related changes and factors causing changes in the system Mandailing of cultural values in the novel Pusara. This type of qualitative research is descriptive by using literature that is novel Pusara as the primary data and supported by secondary data sources. The theory used is a sociological theory of literature that refers to literature Swingewood a social reflection of society, equipped with the concept of culture and cultural change. Mandailing community in the social reality Mandailing still implement custom rules. Dalihan Na Tolu customary institutions still functioned well in traditional ceremonies siriaon (joy) and sidangolon (grief), namely in the ceremony of marriage, birth ceremonies, and funerals. Mandailing community has a habit of travel, like to trade. The results reveal that the contained several novel Pusara forms of Mandailing cultural value system changes. Mandailing cultural value system changes contained in the novel Pusara relates to the reduced role of traditional institutions Dalihan Na Tolu, the implementation of the marriage ceremony where the bride, the ceremony of the birth of the child follow the rules of the Malay culture and Islam, and the implementation of the funerals that follow the teachings of Islam. Mandailing cultural value system changes in the novel Pusara occurs caused by several factors, namely factors intermarriage, adjustment factors teachings of Islam, to custom Mandailing, and factors increasing formal education.